(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with identification of the communicative potential of complex sentences with compliance subordinate which functionate as an independent syntactic unit and as part of a multi-component syntactic structure. The author determines that the syntactical organization of the appropriate form of verbal communication is conditioned by its purpose, functions, and communicative intent of the writer.